Adsorption and molecular dynamics simulations of nonionic surfactant on the low rank coal surface. (1st January 2018) - Lyu, Xianjun; You, Xiaofang; He, Meng; Zhang, Wei; Wei, Hengbin; Li, Lin; He, Qiongqiong
Abstract: Molecular dynamics simulations were carried out to study the behavior of nonylphenol ethoxylate with 12 ethylene oxide groups (NPEO-12) on model surface of Hatcher subbituminous coal. Firstly, in order to verify simulation results, the adsorption experiments between a typical subbituminous coal obtained from Shenhua Shendong Coal Group Corporation Limited in China and NPEO-12 were performed. The thermodynamic functions indicated that the adsorption was a spontaneous process. XPS analysis showed that coverage of the oxygen-containing groups by NPEO-12 improving hydrophobicity of the subbituminous coal. Among these oxygen-containing groups, the adsorption capacity of CO group for NPEO-12 was higher. Afterwards, the interaction of NPEO-12 with the coal surface in aqueous phase was modelled. The surfactant molecules could be detected at the water-coal interface. The water molecules were repelled and stronger hydrophobicity of the coal was obtained in the presence of NPEO-12. The results of aggregated structure of the surfactant molecules on the coal surface in terms of head group and tail group density profiles along the perpendicular direction showed that the ethoxylate groups of the surfactant were attached at the solid surfaces. The negative interaction energy between NPEO-12 and the subbituminous coal surface calculated suggested that adsorption process was spontaneous, which was consistent with the adsorption experiment measurement.